A randomized controlled trial of an mHealth application with nursing interaction to promote quality of life among community-dwelling older adults - Wong, Arkers Kwan Ching; Wong, Frances Kam Yuet; Bayuo, Jonathan; Chow, Karen Kit Sum; Wong, Siu Man; Lee, Athena Yin Lam (Frontiers in Psychiatry, 2022)
Significance: Using mHealth apps alone at home without the support of healthcare experts could mean that older adults might not fully utilize the functions of the apps, recognize their benefits, and sustain their use. Incorporating an integrated health-social partnership model to support the app usage when further help is needed by the older adults might maximize the apps’ benefits in the long term. Objectives: This study aimed to examine the benefits of adding nursing interaction supported by a health-social partnership model in the use of mHealth, and the sustained beneficial effects on psychological outcomes, including quality of life, self-efficacy, and depression, among older adults after the completion of the program. Methods: A three-arm, randomized controlled trial design was adopted. Community-dwelling older adults with chronic pain, hypertension, or diabetes, were randomly assigned to either the mHealth, mHealth with interactivity, or control group. Subjects in both the mHealth and the mHealth with interactivity groups received the mHealth application. In addition, the mHealth with interactivity group received support from a nurse case manager, who was supported by a health-social partnership team. mHealth apps and services from a nurse case manager were not provided to the control group. The primary outcome measure was quality of life, and secondary outcomes were self-efficacy and depression. Data were collected at pre-intervention (T1), post-intervention (T2), and at three months post-intervention to measure the sustained effect of the program. Results: There were 74 mHealth+I, 71 mHealth, and 76 control group subjects enrolled in the program. No statistically significant between-group, within-group, and interaction effects between group and time in both physical component summary (PCS) and mental component summary (MCS) scores were found among the three groups. The mHealth group showed an improvement in PCS and depression scores from T1 to T2, sustained at T3; while the mHealth+I group demonstrated improved self-efficacy from T1 to T2, with a decrease at T3. Conclusion: Adding nurse-directed telephone calls may be of little to no benefit at all in the long term. Future studies may consider a longer intervention period to build and sustain quality of life and self-efficacy levels among community-dwelling older adults.